Políticas públicas e economia solidária: avaliação do projeto sementes da solidariedade - Mota, José Rubens Dutra (2009)
The current essay includes subjects of public policies related to perspectives of the Solidary Economy and sets up as general goal to analyze the conception, suitability and effectiveness of the Public Policy of Support to Solidarity Economy, implemented by the Brazilian Government and taking into account the experience of the Support Program of Solidary Productive Projects executed in the Northeast Region as a supporting the Revolving Solidary Funds. The empirical focus of this essay is the experience of the “Solidary Seed Project”, which purposes to think about agrobiodiversity and the workforce’s autonomy trough the building of Community Seed Houses. This study took account of as basic empirical analysis the experience of Irauçuba, a municipality of the Diocese of Itapipoca, in the State of Ceará. In order to identify the social representations, in terms of social arrangement, we used the qualitative research method. The essay comprises firstly a theoretical discussion, followed by the results of the research applied in the communities of Missi and Bueno. We intended to evaluate the experience in terms of economic, and above all social, environmental and politics effects.